Prime Minister Decree No. 241 of The year 2013 Concerning The Fuel Prices = قرار رئيس مجلس الوزراء رقم 341 لسنة 2013 بشأن أسعار الطاقة / Prime Minister. - Egypt. Prime Minister (2025)
Prime minister decree no. 241 of the year 2013 concerning the fuel prices قرار رئيس مجلس الوزراء رقم 241 لسنة 2013 بشأن أسعار الطاقة